A Case of Unilateral Dermopathy Possibly Related to Graves' Disease. Issue 5 (11th October 2019) - Rodia, Cosimo; Menconi, Francesca; Mazoni, Laura; Torregrossa, Liborio; Basolo, Fulvio; Vitti, Paolo; Marcocci, Claudio; Marinò, Michele
Abstract : Background: The pathogenesis of the extrathyroidal manifestations of Graves' disease (GD) is not fully clarified. According to the most common hypothesis, they would reflect an autoimmune reaction against antigens constitutively expressed by the thyroid and by the extrathyroidal affected tissues. According to another hypothesis, the so-called Kriss' hypothesis, soluble autoantigens released from the thyroid would reach the affected tissues, where they would become the target of the immune system. In this regard, a shift in gravity during sleep may favour antigen deposition. Case Report: A 59-year old man with GD came to our observation because of a dermopathy. He had been treated with radioactive iodine for Graves' hyperthyroidism and with glucocorticoids and orbital decompression for a bilateral Graves' orbitopathy (GO). The patient complained of a monolateral, untreated dermopathy, affecting the left leg and hand. At physical examination the skin of the left pretibial area and of the dorsal surface of the left hand appeared red and thickened, with an orange peel aspect. Interestingly, the patient reported that he usually slept laying on the left side of his body. Discussion: The observation of a patient with a monolateral dermopathy somehow reports to the Kriss' hypothesis, especially in view of the patient's habit of sleeping on the same side as dermopathy was present. Of course, this does not represent a proof that the Kriss' hypothesis is correct, but it carries an element in favour of it. The fact that GO was bilateral is somehow against it, but does not exclude this possibility.